MODERN TECHNIQUES OF TEACHING FUTURE SOCIAL SPHERE WORKERS SPEAKING THE GERMAN LANGUAGE - Iryna Bartosh (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article is dedicated to defining the essence of the notion "social sphere" and outlining the main functions of the social sphere, namely the functions of personality development and social stability, the demographic function as well as the functions of redistribution and economic growth stimulation. The peculiarities of speaking competence as a language process have been also elucidated in the article. Moreover, the article sheds light on the study of the psychological preconditions of the formation of speaking. The article provides an insight into the peculiarities of competence in building up dialogues and monologues and defines the importance of this competence in the career of a social worker. Such types of speaking as a dialogue and a monologue are characterised in the article and it has been proved that these types are the significant aspects in the process of teaching speaking to future workers of the social sphere. In addition, the article outlines the chief methods of teaching communication with the help of dialogues and monologues. The specifics of dialogues and monologues have been analysed from a psychological perspective. The conditions of the successful formation of competence in building up dialogues and monologues have been outlined.